Vehicle Sensor Self-Powered Technology Research Based on Piezoelectric - Sang Ying-Jun; Wu Shangguang; Li Man; Gao Yang; Li Haoxiang; Huang Fei; Hao Yun-Rong; Fan Yuan-Yuan (Institute of Advanced Engineering and Science, 2015)
As a result of the electric vehicles popularity and the development of vehicles intelligent, the number of vehicle sensors surge, meanwhile, many defects of traditional energy supply are increasingly prominent, such as pollution and maintenance difficulties. Taking into account the vehicle vibration exist everywhere, we use the piezoelectric technology to collect vibration energy, and designs a piezoelectric vibration energy harvesting system to be used to solve the energy problem of micro-power sensor. In this paper, the system structure and the theoretical model are analyzed, and the mathematical model of the system vibration frequency and the piezoelectric output have been put forward, then a piezoelectric energy harvesting device is designed on the basis of simulation analysis. Experiments have been done to test the performance of its power generation in the case of resonance. The results showed that the theoretical model proposed in this paper can be a good predictor of the output characteristics of the system. As the resonance frequency is 16.5 Hz, acceleration is 0.5g, the maximum open circuit voltage of the system obtained is 3.5 volts, the optimum load resistance is 425kΩ, and the vibration energy collection device maximum load power is 14 uW. Conclusion: Greater energy could be caught to meet the vehicle sensor power supply needs with the use of super capacitor.